Measuring the Certainty of a Decision Rule with Applications in Electrocardiography - Lesaffre, E.; Willems, J. L. (Methods of Information in Medicine, 1988)
As an extension of recent work, several types of uncertainty involved in a decision process are further clarified in this paper. The concept of allocation with ß-confidence and the ß-doubt matrix are illustrated by two electrocardiographic data sets. These data sets illustrate the importance and the novelty of the above concepts. We argue for augmenting the classical correct classification rate with an interval estimate. We think that interval estimates are essential in the area of prediction modelling to refrain the user from being too optimistic.Als Ausweitung einer früheren Arbeit werden in diesem Artikel diverse Arten der Unbestimmtheit in einem EntScheidungsprozeß weiter abgeklärt. Das Konzept der Zuordnung mit ß-Konfidenz und die ß-Zweifelsmatrix werden an zwei elektrokardiographischen Datensätzen dargestellt. Diese Datensätze veranschaulichen die Bedeutung und die Neuartigkeit der genannten Konzepte. Wir plädieren dafür, die klassische korrekte Klassifikationsrate um eine Intervallschätzung zu vermehren. Wir glauben, daß Intervallschätzungen auf dem Gebiet der Vorhersagemodelle wesentlich sind, um den Benutzer vor zuviel Optimismus zu bewahren.
Keywords: Classification Rate; Electrocardiography; Logistic Models; Medical Decision Making; Sampling Variability